Bartonella endocarditis. Issue 1 (January 2016) - Ghashghaei, Roxana; Thung, Irene; Lin, Grace Y.; Sell, Rebecca E.
Abstract: Blood culture-negative endocarditis presents a clinical and diagnostic challenge. Here, we describe a patient with a delayed diagnosis of Bartonella henselae endocarditis. <Learning objective: The aim of this report is to highlight the importance of Bartonella species as a cause of culture-negative endocarditis and to illustrate the challenges it poses in diagnosis and treatment.>